A High Resolution Method for Fluid Prediction Based on Geostatistical Inversion - Zhen Yu; Jing He (International Journal of Geophysics)
In order to predict the fluid in thin layer precisely, this paper proposed a high-resolution method for fluid prediction. The method used geostatistical inversion with lithology masks to calculate water saturation. We applied this method to theoretical model and real data. The result was compared with that of prestack AVA simultaneous inversion for fluid prediction. It showed that this method had high resolution both in vertical and lateral directions for fluid prediction and could also predict the fluid in thin layer efficiently.